INNOVATIVE DEVELOPMENT OF UKRAINE IN WAR CONDITIONS - TUNITSKA Yuliіa; TUNITSKYI, Nazarii; VARAVA, Vlada (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents a comprehensive study of the key economic and social effects of innovation activity as a determining factor in the structural modernization of the national economy. Ukraine’s position in the international arena in terms of innovation development is identified based on a system of integrated indicators: the Global Innovation Index, the Global Sustainable Competitiveness Index, the Composite Innovation Index, the Global Talent Competitiveness Index, the Global Startup Ecosystem Index, and the Brain Drain Index. A detailed comparative analysis of the financial support for scientific and scientific-technical activities in Ukraine has been carried out, particularly the dynamics of expenditures on innovation as a share of GDP, as well as the structure of financing by sources and sectors, in the context of global trends and EU standards. The article examines the directions of Ukraine’s international innovation cooperation during the period of full-scale invasion, including participation in the Horizon Europe programme, grant projects, and technology transfer initiatives. The peculiarities of innovation development in export-oriented sectors of the economy are studied, and the role of high-tech exports as a driver of national competitiveness is determined. Special attention is devoted to the innovation potential of Ukraine’s defense-industrial complex, in particular the prospects for arms exports as a result of high-technology developments. The preconditions and specific features of innovation activity in the agro-industrial complex are analyzed, and the main stages of agricultural sector development are identified depending on the level of technological modernization. Examples of successful practices of innovation implementation by leading agribusiness companies are provided. Strategic directions for improving the efficiency of Ukraine’s innovation policy in the context of wartime and post-war recovery are substantiated.